Internal CSR Programs in the Context of a Financial Institution Operating in Nepal - Neupane, Pradip; Poudel, Gehanath; Khatiwada, Jhanindra Prasad; Dahal, Rajendra Prasad (International Journal of Atharva, 2024)
This study investigates the internal corporate social responsibility (CSR) practices of employees in commercial banks and explores the relationship between demographic factors and trust. Adopting a quantitative research design, data were collected through a questionnaire distributed to 40 employees representing various levels and departments within the banks. Purposive sampling was utilized, and ethical considerations were strictly followed. Descriptive and inferential statistical analyses were employed to examine the data. Results reveal gender differences in perceptions of company policies, with females generally showing higher agreement on aspects like career development and work-life balance. Married individuals also tended to perceive higher levels of agreement with company policies compared to unmarried counterparts. Moreover, age and years of service exhibited weak negative correlations with various policy aspects, suggesting limited influence on employee perceptions. Overall, the findings emphasize the importance of tailored CSR practices to address diverse employee needs and preferences, irrespective of demographic factors. These insights can inform strategies to enhance employee engagement and organizational performance in commercial banks.